Dampak Rasio Keuangan Dan Good Corporate Governance Terhadap Nilai Perusahaan - Velecia Apriana; Herman Ruslim (Jurnal Manajerial Dan Kewirausahaan, 2021)
This study aims to examine the effect of financial ratios (liquidity, profitability, and free cash flow) and good corporate governance (independent board of commissioners) on firm value by using time-series data of property and real estate companies listed in Indonesia Stock Exchange in the period of 2015-2019. The samples of this study were 33 firms (165 observations). The method used in this study is multiple panel data regression analysis using E-Views 10.0 software. Firm value is measured by Tobin’s Q, liquidity is measured by current ratio, profitability is measured by return on equity, free cash flow is measured by free cash flow ratio, and independent board of commissioners is measured by independent commissioners ratio. The results show that liquidity and free cash flow significantly influence firm value, but profitability and independent board of commissioners do not have any significant influence on firm value. Penelitian ini bertujuan untuk menguji pengaruh rasio keuangan (liquidity, profitability, dan free cash flow) dan good corporate governance (independent board of commissioners) terhadap firm value dengan menggunakan data time-series pada perusahaan property dan real estate yang terdaftar di BEI periode 2015-2019. Sampel pada penelitian ini berjumlah 33 perusahaan (165 observasi). Metode yang digunakan dalam penelitian ini adalah panel data regression analysis menggunakan software E-Views 10.0. Firm Value diukur menggunakan Tobin’s Q, liquidity diukur menggunakan current ratio, profitability diukur menggunakan return on equity, free cash flow diukur menggunakan free cash flow ratio, dan independent board of commissioners diukur menggunakan independent commissioners ratio. Hasil penelitian menunjukkan bahwa liquidity dan free cash flow berpengaruh signifikan terhadap nilai perusahaan, tetapi profitability dan independent board of commissioners tidak berpengaruh signifikan terhadap firm value.